The Corruption Eradication Commission (KPK) Supervisory Board's Role as a Grantor of Permits in Corruption Crimes - Ragil Jaya Tamara; Heni Siswanto; Tri Andrisman; Budi Riski (Faculty of Law, Universitas Lampung, 2021)
The existence of the Corruption Eradication Commission or Komisi Pemberantasan Korupsi (KPK)’s Supervisory Board to oversee KPK's work is the result of the KPK Law Number 19 of 2019. This new legislation mandates the KPK Supervisory Board to perform four primary duties. One of the duties of the Board's authority, permitting or not permitting KPK to conduct wiretapping, search, and/or seizure corruption crimes, sparked public outrage due to the fear of attempts to weaken KPK. This research is served for determining whether the role of the KPK Supervisory Board as a licensee for wiretapping, search, and seizure of criminal acts of corruption is functional and will run effectively and efficiently in tackling the eradication of corruption. The research method used is qualitative research with descriptive presentation and a normative juridical approach. According to the findings, the pro-justice authority delegated by law to the KPK Supervisory Board, namely granting permits for wiretapping, search, and confiscation of criminal acts of corruption, has proven to be effective and efficient in combating corruption. It is concluded because, in principle, it is assumed that balancing all the powers of state institutions through supervision is a natural thing to do.